Competitiveness Position Identification of Indihome Using Service Quality for ISP Dimensions and IPCA Method - Sari Wulandari; Agus Achmad Suhendra; Putra Fajar Alam (School of Business, IPB University (SB-IPB), 2021)
Two major Internet Service Provider (ISP) players, namely Indihome and Firstmedia, experienced a significant increase in traffic. On the other hand, there has been a decline in service quality, due to a spike in the volume of internet usage. The objectives of this study are (1) to identify the strengths and weaknesses of Indihome's fixed broadband services using IPA, (2) to determine the competitive position of Indihome relative to First Media based on Importance Performance Competitor Analysis (IPCA) mapping, (3) to compare the results of evaluating the quality of IPA and IPCA services. The results showed that Indihome has weaknesses in all indicators of Network Quality, 2 indicators of Customer Service & Technical Support (CT6– the ability of CS to resolve complaints, CT3 – CS has product knowledge), and 1 indicator of Security & Privacy (SP1 – security of customer personal data) while the advantages are in 2 indicators of Customer Service & Technical Support (CT2 – completeness of technician installation tools, CT5 – speed of complaint handling), 2 indicators of Security & Privacy (SP2 – transaction data security, SP3 – transaction system security), 1 Information Quality & Website Support indicator (IW4 – channel availability diverse communications), and 1 indicator of Customer Service & Technical Support (CT1 – technician uniform attributes). In addition, the IPCA matrix shows that Indihome's Competitive Position is on the CT2, CT5, IW2 indicators - various payment methods, IW5 - up-to-date information, SP2, and SP3. Based on the comparison of IPA and IPCA data, it is known that there are indicators that perform well when assessed internally but that performance is not better enough when compared to competitors, namely CT1 and IW4. Keywords: internet service provider, service quality, importance performance competitor analysis, competitive position